RELATIONSHIP BETWEEN VITAMIN B12 LEVELS AND ADVERSE LIPID PROFILES IN APPARENTLY HEALTHY INDIVIDUALS VISITING WELLNESS ASSESSMENT CENTER: A PROSPECTIVE STUDY - SHENDE, VIJAYALAXMI (International Journal of Current Pharmaceutical Research, 2024)
Objective: For metabolic disorders, an abnormal lipid profile stands alone as a risk factor. Since most research has been done on unhealthy populations, a relationship in vitamin B12 deficiency and lipid profile is unclear. Methods: We conducted a cross-sectional research with 201 apparently healthy vitamin B12 deficient people, aged 25 to 60, in order to evaluate a relationship in serum vitamin B12 levels and lipid profiles. Results: Sociodemographic, anthropometric, and biochemical data has been collected. Serum vitamin B12 deficiency has defined as serum B12 level of<159 pmol/l.25% of the subjects had raised cholesterol, 70% had raised LDL, 35% had raised triglycerides, and 71% had low HDL. We observed that only MCV was negatively associated with vitamin B12 levels (P<0.0001). A remaining other variables, including lipid profile were not associated with vitamin B12 levels. We also found that presence of comorbidities was not significantly associated with vitamin B12 levels (P=NS). Conclusion: Therefore, in apparently healthy individuals, low serum vitamin B12 levels are not linked with abnormal lipid profiles.